Analysis of platelet function and dysfunction - Jurk, K. (Hämostaseologie, 2015)
Although platelets act as central players of haemostasis only their cross-talk with other blood cells, plasma factors and the vascular compartment enables the formation of a stable thrombus. Multiple activation processes and complex signalling networks are responsible for appropriate platelet function. Thus, a variety of platelet function tests are available for platelet research and diagnosis of platelet dysfunction. However, universal platelet function tests that are sensitive to all platelet function defects do not exist and therefore diagnostic algorithms for suspected platelet function disorders are still recommended in clinical practice.Based on the current knowledge of human platelet activation this review evaluates point-of-care related screening tests in comparison with specific platelet function assays and focuses on their diagnostic utility in relation to severity of platelet dysfunction. Further, systems biology-based platelet function methods that integrate global and specific analysis of platelet vessel wall interaction (advanced flow chamber devices) and posttranslational modifications (platelet proteomics) are presented and their diagnostic potential is addressed.
Keywords: Platelet function; platelet physiology; platelet pathology; point-of-care testing; thrombin; proteomics